Evaluation of in vitro and in vivo potential of Bacillus subtilis MBTDCMFRI Ba37 as a candidate probiont in fish health management. (March 2021) - Nair, Anusree V.; Leo Antony, M.; Praveen, N.K.; Sayooj, P; Raja Swaminathan, T.; Vijayan, K.K.
Abstract: Bacillus subtilis MBTDCMFRI Ba37 ( B. subtilis Ba37), an antibacterial strain isolated from the tropical estuarine habitats of Cochin, was evaluated for in vitro and in vivo potential, and its application as a candidate probiont in fish health management. B. subtilis Ba37 was characterized using their morphological and biochemical properties. It exhibited exoenzymatic activities, tolerance to various physiological conditions and a wide spectrum of antibacterial activity against aquaculture pathogens such as Vibrio and Aeromonas . In co-culture assay, B. subtilis Ba37 inhibited Vibrio anguillarum O1 ( V. anguillarum O1) even with the initial cell count of 10 4 CFUmL −1 . Cytotoxicity assay performed using the cell free supernatant (CFS) of B. subtilis Ba37 revealed its non toxic nature. A twenty one days of feeding trial was conducted in juveniles of Etroplus suratensis ( E.suratensis ) by administrating B. subtilis Ba37 to evaluate its efficacy on growth, immune parameters and antioxidant enzyme activities. Overall the supplementation of B. subtilis Ba37 enhanced significantly ( P  < 0.05) the survival rate, weight gain, specific growth (SGR), feed conversion ratio (FCR), protein efficiency ratio (PER), and feed efficiency (FE) of the fed animals as compared with the control. The immune parameters and antioxidant activities such as total protein, alkaline phosphatase (ALP), superoxide dismutase (SOD) and catalase were also improved significantly ( P  < 0.05) while serum alanine aminotransferase (SGOT) and serum aspartate aminotransferase (SGPT) activities were decreased slightly than the control. After fifteen days of challenge test, the fish fed with B. subtilis Ba37 showed higher relative percentage survival (RPS) than the control. Thus the study indicated the advantages of B. subtilis Ba37 to be used as a candidate probiont, which could be effectively utilized in managing diseases in aquaculture systems and to improve the health of the host. Highlights: B. subtilis Ba37 can be used as a safe candidate probiont in fish health management. It inhibited the growth of aquaculture pathogens viz., Vibrio and Aeromonas sps. Cell free supernatant of this strain was found to be non-toxic to fish cell lines. B. subtilis Ba37 can significantly improve the growth performance of the host. Antioxidant and immune parameters were enhanced in B. subtilis Ba37 fed groups.